Ivermectin and the Integrity of Healthcare Evidence During COVID-19 - O'Mathúna, Dónal P. (Frontiers in Public Health, 2022)
The COVID-19 pandemic has been characterized by a lack of clear evidence to guide healthcare professionals, the public and policymakers. The resulting uncertainty, coupled with changing guidelines as additional evidence became available, added to the stress and anxiety reported by decision-makers. Research results are key to providing evidence to guide healthcare decisions. Important questions have arisen about whether various interventions are safe and effective. The evidence found guides those making treatment decisions, and influences those selecting interventions for further evaluation in research studies. As the COVID-19 pandemic intensified, the effectiveness and safety of many pharmaceuticals was queried. Ivermectin will be used to explore the ethics of how healthcare evidence must be critically appraised, even, or especially, during a pandemic. This drug is alleged to be effective in treating COVID-19, with various studies and systematic reviews finding supportive evidence. Some of these have now been linked to concerns about fraud or poor research reporting. This article will focus on the scientific literature and how apparently fraudulent studies were published and influenced treatment decisions, on-going research and public health guidelines. Research evidence is critical during emergencies like pandemics, but urgency should not overtake ethical responsibilities to critically appraise (or evaluate) studies as they become available. These responsibilities apply in various ways to editors, peer-reviewers, news media reporters, and those making treatment decisions, including clinicians, policymakers and the general public. While research article authors have the primary ethical responsibility to reject fraudulent or inaccurate claims, the readers of health research must carefully evaluate all publications. To detect and reject fraudulent healthcare claims, readers need critical appraisal skills that match their level of engagement with those articles. The core principles of critical appraisal will be described in the article, and how they can be adapted for different types of readers. Exemplar tools that develop critical appraisal skills will be noted, with reviews of ivermectin's efficacy explored as examples. As stakeholders in healthcare evidence are increasingly able to identify well-conducted and ethical research they will simultaneously be able to spot and reject fraudulent reports and prevent them from influencing healthcare decisions.